Book review:Piotr L. GROTOWSKI. Arms and Armour of the Warrior Saints: Tradition and Innovation in Byzantine Iconography (843-1261). Translated by Richard Brzezinski. Leiden, Boston: Brill, 2010. - TSURTSUMIA, Mamuka (Byzantina Symmeikta, 2012)
Book review of:Piotr L. Grotowski. Arms and Armour of the Warrior Saints: Tradition and Innovation in Byzantine Iconography (843-1261). Translated by Richard Brzezinski. Leiden, Boston: Brill, 2010. pp. XXV, 483. ISBN 978 90 04 18548 7.